(untitled) (Journal of Economic Research & Business Administration, 2020)
The purpose of the study – reflects a study of the methodology of the process of determining the tax base when calculating corporate income tax on (example of the construction company “XXX”). Identification of the main problems in calculating income tax and advance payments. Originality / value – the basic aspects of the taxation process are noted. To clearly reflect the process of determining income tax as a research base, we analyzed data on the financial and tax reporting of a construction company. An example of determining income tax and calculating advance payments is given. Recommendations on tax accounting, including for construction companies, are developed, specific aspects of taxation in this industry are indicated. Conclusions – the need for improving the tax accounting methodology has been identified and suggestions have been developed to achieve the goal of the study. The practical significance of the article will allow accounting and auditing services to take into account the main points in determining the tax base and drawing up the tax accounting policy in terms of corporate income tax. Features of tax accounting in construction makes it possible to disclose the specifics of determining the tax base for corporate income tax for Kazakhstan companies.